ANALISA STATUS LUAR FORMASI SERTA DAMPAKNYA TERHADAP PERSONEL DAN INSTITUSI AKADEMI MILITER - Mega, Aryanti; kartikasari, windy; Roro Ratih Ayu Mustika Sari (JURNAL DWIJA KUSUMA, 2023)
The condition in which there are some personnel who have positions and those who don't will rise questions about how many personnel who will not get position, the factors that cause it and the effect that will happen to the organization's performance. The purpose of this study is to see the impacts resulted by personnel who have position outside of formation to the Military Academy. This research is using descriptive qualitative data collection techniques by conducting interviews, documentations and observation. In the end of this study, it can be stated that the one who has position outside of the organization formation does not have a significant impact on the performance of the Indonesian Military Academy in carrying its main task.